Schizophrenia and Hyperostosis Frontalis Interna with History of Head Injury - Fatima Elghazouani (Case Reports in Medicine)
Hyperostosis frontalis interna is an irregular thickening of the frontal bone. Its etiology is unknown. It has been rarely linked with schizophrenia and head injury. Case Presentation. We describe an unusual case of a 44-year-old female with schizophrenia and hyperostosis frontalis interna having a history of head trauma. At the age of 3 years, she had a head injury that could be classified as mild traumatic brain injury. She presents a family history of schizophrenia. She was admitted for resistant schizophrenic disorder. The cranial computed tomography showed bilateral and asymmetrical hyperostosis of the frontal bone that was more pronounced on the right side. This corresponds to the impact of the trauma with frontal atrophy without any metabolic or endocrinal abnormalities. Conclusion. We surmise that the long-term pathological effects of traumatic brain injury, including hyperostosis frontalis interna, are likely to interact with genetic vulnerability and may lead to schizophrenic disorder.